The doctrine in power and the origins of the doctrine dirigée: the early role of the Soviet legal doctrine through the official legal journal of the RSFSR (1918-1922) - Marco Mellina (Clio@Themis)
Analysing data about articles and authors from the official legal journal of the Russian Soviet Federative Socialist Republic, Proletarian Revolution and Law, this article shows that the legal doctrine writing in the journal was primarily composed by jurists who were also part of the ruling class from 1918 to 1921, effectively creating a doctrine in power. This observation partly contrasts with the dominant Western historiographical notion of Soviet legal doctrine being only directed by an external political power. However, the article also shows how, with the advent of the NEP, the establishment of the USSR, the revival of law and the consequent proliferation of legal journals, Soviet legal doctrine expanded and laid the foundations for the doctrine dirigée of later years.